Towards eradication of HBV: Treatment approaches and status of clinical trials. (October 2021) - Sandmann, Lisa; Cornberg, Markus
Abstract: Chronic hepatitis B virus (HBV) infection and its sequelae remain a global health challenge. Current treatments are effective in controlling HBV replication, but complete eradication or 'cure' of HBV remains a rare event and is difficult to assess because of the intrahepatic reservoir of covalently closed circular DNA. Based on the understanding of the HBV life cycle and the deciphering of immune responses to HBV, therapeutic strategies to target HBV eradication are in principle possible. This article reviews current developments in new therapies aimed at HBV cure.